2019
DOI: 10.7575/aiac.alls.v.10n.2p.56
|View full text |Cite
|
Sign up to set email alerts
|

Factors Causing Demotivation in EFL Learning Process and the Strategies Used by Turkish EFL Learners to Overcome their Demotivation

Abstract: The purpose of the current study is to determine main demotivating factors affecting Turkish EFL university students’ English language learning process and to identify the ways they apply to cope with these negative experiences from their own perspectives. The participants were 469 first and second year Turkish EFL university students. Both quantitative and qualitative methods were used to collect data in the study. First, a demotivation questionnaire (Sakai & Kikuchi, 2009) was administered to the partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…In addition, teachers' behavior can affect students' demotivation. The findings of Han et al (2019) show that teachers' negative reaction toward students' mistakes may make them less eager to speak and demotivated. In addition, remark that teachers' attitudes such biased behavior, indifference, and unintelligible teaching methods can lead to students' demotivation (Hassaskhah et al, 2015).…”
Section: Teachers' Competence and Teaching Stylesmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, teachers' behavior can affect students' demotivation. The findings of Han et al (2019) show that teachers' negative reaction toward students' mistakes may make them less eager to speak and demotivated. In addition, remark that teachers' attitudes such biased behavior, indifference, and unintelligible teaching methods can lead to students' demotivation (Hassaskhah et al, 2015).…”
Section: Teachers' Competence and Teaching Stylesmentioning
confidence: 98%
“…Furthermore, physical facilities can affect students' level of motivation and academic performance (Akomolafe & Adesua, 2016). Although several studies on demotivation do not suggest inadequate school facilities as the most salient demotivation factors (Ghadirzadeh et al, 2013;Han et al, 2019;, numerous research show that inadequate school facilities can be the most demotivating factors (Adara et al, 2019;Krishnan & Pathan, 2013;Meshkat & Hassani, 2012;Rajabi & Pozveh, 2016). This difference may be attributed to the availability of The availability of adequate school facilities may differ from one institution to another.…”
Section: Inadequate School Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although paying too much attention to errors may be counterproductive when assessing translation students -especially when addressing motivation issues as already investigated in the area of English Language Teaching (see, for example, Han et al, 2019)-it is extremely important to make students aware of inadequacies so that they can place themselves in their own learning map and also find more appropriate solutions to the task at hand. Nevertheless, in order to avoid excessive error marking, teachers may want to focus on what the target text should convey instead of making students too attached to the source text.…”
Section: Translation Errormentioning
confidence: 99%
“…While Setyowati and Firmansyah (2018), and Suwarna (2001) found that social studies learning is more memorized and monotonous, does not make students think critically so that it seems to saturate. Monotonous learning can affect learning objectives (Han, Takkaç-Tulgar, & Aybirdi, 2019).…”
Section: Introductionmentioning
confidence: 99%